Magmatism in the Asunción-Sapucai-Villarrica Graben (Eastern Paraguay) Revisited: Petrological, Geophysical, Geochemical, and Geodynamic Inferences. (15th May 2013) - Comin-Chiaramonti, Piero; De Min, Angelo; Cundari, Aldo; Girardi, Vicente A. V.; Ernesto, Marcia; Gomes, Celso B.; Riccomini, Claudio
Abstract : The Asunción-Sapucai-Villarrica graben (ASV) in Eastern Paraguay at the westernmost part of the Paraná Basin was the site of intense magmatic activity in Mesozoic and Tertiary times. Geological, petrological, mineralogical, and geochemical results indicate that the following magmatic events are dominant in the area: (1) tholeiitic basalt and basaltic andesites, flows and sills of low- and high-titanium types; (2) K-alkaline magmatism, where two suites are distinguished, that is, basanite to phonolite and alkali basalt to trachyte and their intrusive analogues; (3) ankaratrite to phonolite with strong Na-alkaline affinity, where mantle xenoliths in ultramafic rocks are high- and low-potassium suites, respectively. The structural and geophysical data show extensional characteristics for ASV. On the whole, the geochemical features imply different mantle sources, consistently with Sr-Nd isotopes that are Rb-Nd enriched and depleted for the potassic and sodic rocks, respectively. Nd model ages suggest that some notional distinct "metasomatic events" may have occurred during Paleoproterozoic to Neoproterozoic times as precursor to the alkaline and tholeiitic magmas. It seems, therefore, that the genesis of the ASV magmatism is dominated by a lithospheric mantle, characterized by small-scale heterogeneity.